QED corrections to radiative recombination and radiative decay of heavy hydrogenlike ions - Holmberg, Johan; Artemyev, Anton; Surzhykov, A.; Yerokhin, V. A.; Stöhlker, Th. (Physical review. A, Atomic, molecular, and optical physics, 2015)
One-loop quantum electrodynamic (QED) corrections are studied for two basic atomic processes, radiative recombination of an electron with a bare nucleus and radiative decay of a hydrogenlike ion. The perturbations of the bound-state wave function and the binding energy due to the electron self-energy and the vacuum polarization are computed in the Feynman and Coulomb gauges. QED corrections induced by these perturbations are calculated for the differential cross section and the polarization of the emitted radiation in the radiative recombination of an electron and a bare uranium nuclei, as well as the corresponding corrections to the ratio of the E1 (electric dipole) and M2 (magnetic quadrupole) transition amplitudes in the 2p3/2→1s radiative decay of hydrogenlike uranium. The results obtained indicate the expected magnitude of the QED effects in these processes on a subpercent level.